Spectral Characteristics of Vowels (Monophthongs) in Modem Lithuanian - Balšaitytė, Danutė (Respectus Philologicus, 2004)
Many studies that deal with the vocalism in codified Lithuanian focus mainly on the phonological interpretation of vowels, their distinctive features, and on the description of articulation of individual sounds, while acoustic properties of the Lithuanian vowels have not been explored at large. The present article offers the results of phonetico-experimental analysis of acoustic parameters (formant structure and duration) of the basic allophones of the Lithuanian monophthongs in the acoustic space and shows the correlation between the length/shortness and the formant structure of the vowels.